Barriers to online tax filing a contextual analysis of SMEs in Tacloban City - Burato, Elvan M.; Enero, Ma. April Joy D.; Makinano, Nic Daren C.; Silawan, Nelson Anthony B. (Division of Management, University of the Philippines Tacloban College, 2025)
This study explores the barriers to the adoption of online tax filing systems among Small and Medium Enterprises (SMEs) in Tacloban City, Philippines. While existing literature identifies common barriers such as technical, financial, institutional, knowledge and awareness, perceived complexity, and psychological challenges, this study reveals additional cultural barriers unique to Tacloban. Key technical barriers include unreliable internet access, while financial constraints, such as the costs of necessary technology, also impede adoption (Sapari et al., 2024). Institutional barriers, including low trust in government systems, and psychological barriers, like fear of making errors in online filing, further hinder SMEs (Rey et al., 2024). Furthermore, a lack of knowledge and awareness about the digital filing systems contributes to reluctance (De Castro et al., 2015). However, the study highlights a significant cultural barrier, with SMEs showing some preference for traditional face-to-face interactions, due to the historical struggle from Typhoon Yolanda (Florano, 2023). This cultural resistance, combined with the other barriers, significantly slows the adoption of online tax systems. The study emphasizes the need for a comprehensive approach to overcome these barriers, including cultural sensitivity, enhanced digital literacy programs, infrastructure improvements, and targeted government engagement. The findings offer valuable insights for policymakers, suggesting strategies that address both the technical and cultural challenges to improve online tax filing adoption in Tacloban and similar regions.